Propriedades físicas de um latossolo vermelho cultivado no sistema plantio direto - da Silva, Fernanda de Fátima [UNESP] (2008)
The pressure caused by agricultural machinery traffic many result in soil compactation in no-tillage system. The aim of this work was to evaluate no-tillage system onset,time on some physical properties, index S and organic matter (OM) of an oxysol located in Jaboticabal, Sao Paulo State, Brazil. The experiment had completely randomized split-splot design. The treatments consisted of four no-tillage systems: no-tillage for 2 years, no-tillage for 4 years, no-tillage for 6 years and one natural wooded area. The evaluated layers were: Q-0.10m, 0.10-0.20m and 0.20-030m. The following were determined: soil porosity, soil aggregates, bulk density, index S and organic matter. The results were submitted to variance analysis and when there was a difference between averages, Tukey's test was used to compare them. The natural wooded area showed higher organic matter, macroporosity, hydraulic conductivity and Index S. There was no difference between the studied parameters, showing that the no-tillage system for six years was not enough to change the soil physical property.